(untitled) (Research, Society and Development, 2021)
The study aimed to identify the need for school adaptations for children with ASD, to facilitate the teaching and learning process. It is predominantly quantitative, descriptive field research. It was held in a municipal teaching institution in Teresina-PI, with 3 teachers, where it will be necessary to work at the institution for more than a year and have autistic students in their classes. Data collection was performed through the application of a questionnaire prepared by the researcher online, using the Google Forms platform and sent through Gmail and Outlook. The variables present in this questionnaire were: the recognition of the theme, the importance of making these adaptations, and the teachers’ doubts. The data were subjected to content analysis, later organized in graphics of the Microsoft Excel 2016 program. The article reports the existence of difficulty for teachers to pass on activity to students with ASD, in which (67%) corresponding to 2 teachers, of a sample of 3 teachers reported to exist very often, in addition to demonstrating that children with ASD are able to perform activities without adequate adaptation, infrequently, according to 100% of the sample, with this it is also observed that teachers have little ( 67%) or no (33%) training for curricular adaptations for their students with ASD. In addition to being possible to verify the frequency with which the school does not provide materials for adaptations to occur for students with ASD, where it is verified that 67% of the sample (3 teachers) claim to be infrequently. Thus, the need for adaptations is notable, in addition to the lack of preparation of teachers and the lack of support from the school, and the importance of these adaptations for students with ASD.